Phylogeographic patterns of diversification in three saxicolous small mammals Micaelamys namaquensis Smith, 1834 (Rodentia: Muridae), Procavia capensis Pallas, 1766 and Heterohyrax brucei Gray, 1868 (Hyracoidea: Procaviidae) of South Africa - Bloomer, Paulette (University of Pretoria, 2026)
Thesis (PhD (Zoology))--Univeristy of Pretoria, 2019